Signaling ideology through consumption - Florian H. Schneider (University of Zurich, Department of Economics, 2022)
Firms often discourage certain categories of individuals from buying their products, seemingly at odds with typical assumptions about profit maximization. This paper provides a potential rationale for such firm behavior: Consumers seek to signal that they have "desirable" ideological values to themselves and others by avoiding products popular among people with "undesirable" values. In laboratory experiments and surveys, I provide causal evidence that consumption can be diagnostic of consumers' ideologies and that demand for a product is lower if its customer base consists of individuals whose ideological values are widely considered undesirable. These effects occur for both observable and unobservable consumption and for products that do not possess any inherent ideological or undesirable qualities.
Keywords: D12; C91; M3; 330; Ideology; social image; self-image; signaling; consumption; experiments